2011
DOI: 10.1021/ie200515g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of the Free-Radical Process during the Initiated Thermal Cracking of Normal Alkanes with 1-Nitropropane as an Initiator

Abstract: To elucidate the accelerating effect of 1-nitropropane on the thermal cracking of normal alkanes, ab initio and density functional theory calculations were performed to investigate the elementary reactions involved in the initiated thermal cracking of a 1-nitropropane/n-heptane mixture. The kinetic parameters were evaluated on the basis of standard transition state theory (TST) or variational transition state theory (VTST) with Wigner tunneling correction. The activation energy for the C–N bond rupture of 1-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 73 publications
0
3
1
Order By: Relevance
“…This is due to the scission of weak C–N bonds in the molecules to generate alkyl and amino radicals, which initiate fuel cracking at relatively low temperatures. Similarly, organic amines, including octadecylamine, tributylamine, triethylamine, and hyperbranched poly-(amidoamine) (CPAMAM), have been reported to be effective in enhancing the cracking of hydrocarbon fuels. ,, It is noted that the promotion effect of ILs in our case is not as good as the previously reported organic amines, which could be ascribed to a low concentration of ILs and the robust imidazole ring.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…This is due to the scission of weak C–N bonds in the molecules to generate alkyl and amino radicals, which initiate fuel cracking at relatively low temperatures. Similarly, organic amines, including octadecylamine, tributylamine, triethylamine, and hyperbranched poly-(amidoamine) (CPAMAM), have been reported to be effective in enhancing the cracking of hydrocarbon fuels. ,, It is noted that the promotion effect of ILs in our case is not as good as the previously reported organic amines, which could be ascribed to a low concentration of ILs and the robust imidazole ring.…”
Section: Resultscontrasting
confidence: 59%
“…Symmetrical imidazolium ionic liquids (ILs) have high thermal stability, high hydrocarbon solubility, and strong binding ability to metal nanoparticles. In addition, the C–N in the imidazolium group would also initiate the cracking by providing radicals as alkylamines and hyperbranched CPAMAM polymer. ,, Based on these, we propose to prepare hydrocarbon-soluble metal nanoparticles by using symmetrical imidazolium ionic liquids as protective agents in this work. The symmetric 1,3-bis­(14-alkyl) imidazolium ionic liquid was chosen due to its conjugated imidazole ring with C–N bonds and symmetric long-chain alkyl groups at the 1st and 3rd positions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The satisfactory model prediction of the experimental measurements allowed the kinetic effect of nitromethane initiation on n -decane pyrolysis to be analyzed. Guan et al , explored the effect of nitroalkane initiators on the cracking of C7 alkanes using quantum chemical calculations and reactive molecular dynamics simulations, respectively. Reasonable Arrhenius parameters estimated from reactive molecular dynamics simulations compared well with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty et al 24 found that the added initiator had an effect when the fuel pyrolysis rate was low, and its effect was negligible when the fuel pyrolysis rate was high. Guan et al 26,27 studied the initial pyrolysis path of n-alkane/nitro-alkane-initiated pyrolysis by the quantum chemical calculation method and obtained four possible initial reactions according to the calculation results of activation energy. In summary, the previous research on initiated pyrolysis focuses on macroscopic aspects such as improving the fuel pyrolysis rate and heat sink.…”
Section: Introductionmentioning
confidence: 99%